The incidence of potato virus Y strains in Slovenia - Peter DOLNIČAR (Acta Agriculturae Slovenica, 2004)
The incidence of potato virus Y (PVY) strains and its infection pressure across Slovenia were monitored. Disease free tubers of the variety Igor were planted on different locations across Slovenia in 1997, 1998 and 2000. Tubers were harvested and visually evaluated for the presence of necrosis. They were tested by means of ELISA using polyclonal antibodies of PVY and  monoclonal antibodies PVYN of Bioreba, and PVYN, PVYO and PVY O/C of Adgen. PVY NTN was the predominant strain on all locations in 1997 and 1998. The highest infection with PVYO  was found in Pivka and Rakičan in the year 2000. PVYC strain was not found during the study. The infection with PVY was smaller in isolated parts of Slovenia like Brezula, Podčetrtek, Trbonje, Libeliče, Vrtojba and Tolmin. It also decreased from 1997 to 2000.